THE EFFECT OF REGULAR QUIZZES TOWARDS STUDENTS’ ACHIEVEMENTIN A CONTENT-BASED SUBJECT - Lely Refnita (English Language Teaching and Research, 2017)
This paper is derived from the result of an experimental research on the effect of giving weekly quizzes as a formative assessment towards students’ achievement. The research was done during the odd semester of 2016/2017 academic year at the English Department of Bung Hatta University. The sample that comprised 52 students was chosen by using total sampling technique. The one-shot case study design was considered suitable for both the type of sample and the research problem and thus applied in the study. After the treatment in the form of giving a ten-item-matching quiz at the end of every instructional meeting, the data were collected by using a posttest and then analyzed by using a t test for non-independent sample. The result of data analysis showed that the value of t-calculated was bigger than that of t-table; therefore, it can be concluded that giving regular quizzes was an effective way to improve students’ achievement. Key words: effect, quiz, achievement, content-based subject